A Seismic Approach to Flood Detection and Characterization in Upland Catchments. Issue 20 (17th October 2022) - Dietze, M.; Hoffmann, T.; Bell, R.; Schrott, L.; Hovius, N.
Abstract: About 10% of Europe's surface area is prone to rapid flooding of rivers confined in valleys. The devastating potential of such floods is exacerbated by the deficits of existing gauging networks, including low station densities and recording frequencies, and lack of information beyond stage height. Here, we use seismic data of the July 2021 Ahrtal flood, Germany, to extract information to complement sparse hydrometric data, and to reconstruct the rapid evolution of this fatal event. We show that a seismic station can deliver essential flood metrics such as magnitude, propagation velocity and debris transport rate. These seismic products provide high resolution insight to the non‐linear flood behavior. We argue that an approach combining distributed low‐cost seismometers with existing seismic stations, can provide important real time data on future catastrophic floods and associated hazards in upland catchments, offering precious response time also in currently ungauged landscapes. Plain Language Summary: Rapidly evolving floods are a major hazard for 10% of European landscapes. They are hard to adequately detect and describe by the classic gauge station scheme, but seismic sensors provide a valuable alternative to this difficulty. A seismometer can sense a flood like the devastating one that hit the Ahr valley, Germany, in July 2021 up to 1.5 km away. The seismic footprint of the flood allows to provide information on flood magnitude, velocity and trajectory at sub‐minute resolution and at near real time. We show how this new approach can be utilized for future flood protection. Key Points: Seismic sensing of valley confined floods improves classic detection approaches Near‐real time information on flood magnitude, trajectory, and velocity Gate keeper seismometer networks can improve flood risk management in Europe